2021
DOI: 10.1038/s41416-021-01477-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtype-specific efficacy of anti-EGFR therapy in colorectal cancer is dependent on the chemotherapy backbone

Abstract: Background Patient selection for addition of anti-EGFR therapy to chemotherapy for patients with RAS and BRAF wildtype metastatic colorectal cancer can still be optimised. Here we investigate the effect of anti-EGFR therapy on survival in different consensus molecular subtypes (CMSs) and stratified by primary tumour location. Methods Retrospective analyses, using the immunohistochemistry-based CMS classifier, were performed in the COIN (first-line oxalipla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
(66 reference statements)
3
13
1
Order By: Relevance
“…Interestingly, in the remaining two of the paired samples (FC‐6‐0005 and FC‐6‐0006), the GEPs changed from the TA/enterocyte subtypes to stem‐like subtypes after FC‐6 treatment. It is worth noting that FC‐6‐0005 and FC‐6‐0006 switched from TA/enterocyte subtypes with good/intermediate outcomes to stem‐like with a very poor prognosis 29 and are associated with lack of efficacy to EGFR inhibitors when combined with an oxaliplatin chemotherapy backbone 30 …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in the remaining two of the paired samples (FC‐6‐0005 and FC‐6‐0006), the GEPs changed from the TA/enterocyte subtypes to stem‐like subtypes after FC‐6 treatment. It is worth noting that FC‐6‐0005 and FC‐6‐0006 switched from TA/enterocyte subtypes with good/intermediate outcomes to stem‐like with a very poor prognosis 29 and are associated with lack of efficacy to EGFR inhibitors when combined with an oxaliplatin chemotherapy backbone 30 …”
Section: Resultsmentioning
confidence: 99%
“…CMS2 is an over-activated epithelial growth factor pathway with higher expression of EGFR and the EGFR-ligands amphiregulin and epiregulin, that are correlated to an increased response to EGFR inhibitor therapy in RAS/BRAF wt CRC (17) analyzing gene signature of 514 samples of patients enrolled in the FIRE-3 study, demonstrated that patients with CMS4 tumors had a longer OS when treated with cetuximab vs bevacizumab (18). In another molecular analysis of RAS/BRAF wt patients from the COIN and PICCOLO study, patients with CMS4 tumors showed a a longer OS and PFS when treated with anti-EGFR-based treatment vs chemotherapy alone (19).…”
Section: Discussionmentioning
confidence: 99%
“…Stintzing et al., analyzing gene signature of 514 samples of patients enrolled in the FIRE-3 study, demonstrated that patients with CMS4 tumors had a longer OS when treated with cetuximab vs bevacizumab ( 18 ). In another molecular analysis of RAS/BRAF wt patients from the COIN and PICCOLO study, patients with CMS4 tumors showed a a longer OS and PFS when treated with anti-EGFR-based treatment vs chemotherapy alone ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…13 However, other studies have shown no survival benefits associated with EGFR inhibitor therapy in patients with a KRAS-WT tumor 14 or varying efficacy of EGFR inhibitors by chemotherapy backbone. 15 With VEGF inhibitors, a meta-analysis of 7 RCTs that included 2040 patients with mCRC reported that VEGF inhibitor therapy was associated with improved progression-free survival time, but not with overall survival. 16 Another study pooling data from 9 trials comprising 3914 patients noted that the addition of VEGF inhibitors to various chemotherapy regimens was associated with higher progression-free survival, as well as higher overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, among patients with RAS- WT tumors, studies have shown survival advantage with the addition of EGFR inhibitors to a chemotherapy backbone, such as FOLFOX (folinic acid, fluorouracil, and oxaliplatin) or FOLFIRI (folinic acid, fluorouracil, and irinotecan) . However, other studies have shown no survival benefits associated with EGFR inhibitor therapy in patients with a KRAS -WT tumor or varying efficacy of EGFR inhibitors by chemotherapy backbone …”
Section: Introductionmentioning
confidence: 99%